The Character of the Prophet Muhammad in Objective Exegesis (A Comparative Study Between Allama Ja’far Sobhani and the Thinker Samih Atif Al-Zein) - صفدري شكرية سادات; مكصوصي عذراء جاسم عبد (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The distinguished scholar Sheikh Ja’far Al-Subhani and Dr. Samih Atif Al-Zein are among the prominent scholars who have made significant contributions to the scientific discourse in the field of thematic interpretation. This research is an attempt to conduct a comparative methodological study of the approaches used by Sheikh Ja’far Al-Subhani and thinker Samih Atif Al-Zein in their approaches to thematic interpretation. The researcher relied on the inductive method in this study by collecting the views and concepts expressed by both esteemed scholars on the thematic interpretation of the Prophet’s character and biography through their prominent works, "Concepts of the Qur’an" by Sheikh Ja’far Al-Subhani and "Thematic Interpretation" by Samih Atif Al-Zein. The study covered what these two scholars wrote on thematic interpretation, including the doctrinal, behavioral, and political dimensions of the biography of the noble Prophet (peace and blessings be upon him and his family). The research also addressed the points of agreement between the two scholars, Al-Subhani and Samih Atif, who concurred that the personality of the Prophet (peace and blessings be upon him and his family) originates from a methodology of self-purification and the building of a legitimate family characterized by noble origin and enduring dignity, which upholds the honor of Muslims and prevents humiliation. His heavenly justice combats oppression and corruption, promotes affection among Muslims, respects others, and honors humanity.